PENGARUH KOMPETENSI KARYAWAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING (Studi Pada PT. Krakatau Bandar Samudera) - Basori, Miftahul Ainun Naim; Prahyawan, Wawan; Kamsin, Daenulhay (Jurnal Riset Bisnis dan Manajemen Tirtayasa, 2017)
Employee Performance PT. Krakatau Bandar Samudera in 2016 does not match the company target as stated in Work Plan and Corporate Budget (RKAP) year 2016. It can be caused by Employee Competency factor which still not yet reached the competency gap and Working Environment of company located in working area of port. The purpose of this study is to analyze the influence of Employee Competence and Work Environment on Employee Performance through work motivation as intervening variable. With the implementation of this research is expected to provide theoretical benefits for academics and practical for PT. Krakatau Bandar Samudera. This research method uses quantitative method by using deductive way of thinking, that is seeing pattern which is common to special. To achieve the expected research target, the researcher collected primary data with questionnaire technique of semantic differential to 83 respondents and data analysis technique with Partial Least Square (PLS) software. The result of the research shows that Employee Competence and Work Environment do not have an effect on Employee Performance directly but result show that there is influence after tested by intervening variable of Work Motivation.